Makna lirik lagu beranjak dewasa oleh nadin amizah kajian teori hermeneutika schleiermacher - Mellyka Maharani Jatmiko; Latifa Ramonita (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The process of transitioning into adulthood is a complex phase characterized by emotional instability, identity negotiation, and psychological uncertainty, particularly among Generation Z. Popular music often functions as a reflective medium that articulates such experiences, one of which is expressed through the song Beranjak Dewasa by Nadin Amizah. This study aims to analyze the meaning embedded in the song’s lyrics using Schleiermacher’s hermeneutic approach, which emphasizes grammatical and psychological interpretation.This research employs a qualitative descriptive method through textual analysis of selected lyric excerpts that represent the process of individual maturation. The findings indicate that the song’s lyrics portray inner conflict, emotional vulnerability, acceptance of change, and awareness of life’s imperfections as integral parts of becoming an adult. Grammatically, the song uses simple yet emotionally rich diction, creating an intimate and reflective tone, while psychologically, the lyrics reflect the songwriter’s subjective emotional experiences. This study contributes to the fields of communication and popular music studies by demonstrating the relevance of hermeneutic analysis in interpreting contemporary song lyrics and by providing insights into the representation of the quarter-life crisis in Indonesian popular music narratives